2023
DOI: 10.1177/17588359231152839
|View full text |Cite
|
Sign up to set email alerts
|

Targeting lipid metabolism in metastatic prostate cancer

Abstract: Despite key advances in the treatment of prostate cancer (PCa), a proportion of men have de novo resistance, and all will develop resistance to current therapeutics over time. Aberrant lipid metabolism has long been associated with prostate carcinogenesis and progression, but more recently there has been an explosion of preclinical and clinical data which is informing new clinical trials. This review explores the epidemiological links between obesity and metabolic syndrome and PCa, the evidence for altered cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 249 publications
0
8
0
Order By: Relevance
“…Scheinberg et al summarized the relationship between dietary fat intake and the risk of PCa and found contradicting results from various studies. Possible mechanisms by which fat intake increases the occurrence of PCa include the effects on hormone regulation and androgen levels, oxidative stress, inflammation, exposure to toxic pesticides, and the effects of specific fatty acids 78 . Another review suggested that reducing red meat and saturated fat intake could prevent PCa.…”
Section: Some Elements That Indirectly (Through Ppat) or Directly Aff...mentioning
confidence: 99%
See 2 more Smart Citations
“…Scheinberg et al summarized the relationship between dietary fat intake and the risk of PCa and found contradicting results from various studies. Possible mechanisms by which fat intake increases the occurrence of PCa include the effects on hormone regulation and androgen levels, oxidative stress, inflammation, exposure to toxic pesticides, and the effects of specific fatty acids 78 . Another review suggested that reducing red meat and saturated fat intake could prevent PCa.…”
Section: Some Elements That Indirectly (Through Ppat) or Directly Aff...mentioning
confidence: 99%
“…Similar trends were observed for aggressive disease and death. However, these studies could not reproduce each other's findings because it is difficult to compare between trials owing to differences in study methods, assays, and metabolites examined 78 . Overall, these results suggested that PPAT-related genomic and lipid metabolomic profiles have critical potential applications for diagnostic applications.…”
Section: Ppat Provides New Perspectives For Diagnosing and Treating P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Statins are currently the primary treatment agents for aberrant lipid metabolism; however, it is uncertain whether the use of statins increases the risk of developing PCa (153). Some studies (154)(155)(156)(157) have demonstrated that there is no association between statin use and the risk of developing PCa, while other studies (158)(159)(160) have indicated that statin use reduces the risk of developing advanced PCa and the risk of fatal PCa.…”
Section: Lipid Metabolism and The Diagnosis And Treatment Of Prostate...mentioning
confidence: 99%
“…Specifically, alterations in lipid metabolism can promote tumor cell growth, invasion, and metastasis, and regulate the characteristics of the tumor microenvironment through intracellular signaling pathways ( 9 , 10 ). Changes in lipid metabolism have been confirmed to be associated with tumor growth and treatment response in various cancers, including colorectal cancer, pancreatic cancer, and prostate cancer ( 11 - 13 ). However, the alterations in lipid metabolism in GC and whether these changes can serve as prognostic biomarkers have not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%